Crimean-Congo haemorrhagic fever: an overview - Agravat, Virat J.; Agarwal, Sneha; Piparva, Kiran G. (International Journal of Research in Medical Sciences, 2017)
Crimean-Congo Hemorrhagic Fever (CCHF) is an acute, highly-contagious and life-threatening vector borne disease. The CCHF virus causes severe viral hemorrhagic fever outbreaks, with a case fatality rate of 10-40%. CCHF virus isolation and/or disease has been reported from more than 30 countries in Africa, Asia, South eastern Europe and Middle east. Jan 2011 marks first ever reports of outbreak of CCHF in India, total 5 cases were detected of CCHF from Gujarat. CCHF has recently in news again, 6 human cases and 32 animal samples test positive for CCHF from Kariyana village of Amreli district (Gujarat state) July 2013. Crimean-Congo hemorrhagic fever virus (CCHFV), member of genus Nairovirus in the family Bunyaviridae. Numerous genera of ixodid ticks serve both as vector and reservoir for CCHFV. Human infections occurred through tick bites, direct contact with blood or tissue of infected livestock, or nosocomial infections. Human infections begin with nonspecific febrile symptoms, but progress to a serious hemorrhagic syndrome with a high case fatality ratio. The most definitive way of diagnosis is the demonstration of virus or viral genome in sera samples. Hospitalization in special care unit with constant effort to prevent haemorrhagic complication along with laboratory monitoring is cornerstone for treatment of CCHF. Till date there is no FDA approved drug or definitive treatment for CCHF, ribavirin is tried by many physician need to be evaluated further. Current article is an effort to update existing knowledge about CCHF by due focus on various aspects especially prevention of this zoonotic disease. Much of the real life queries about this disease are elaborated after extensive literature research.